CYTOMEGALOVIRUS IgG AND IgM ANTIBODIES AMONG SUDANESE PATIENTS WITH ACUTE MYELOID LEUKEMIA: RELATION TO HEMATOLOGICAL PROGNOSTIC MARKERS - O M AbuAlas, Elamin; Mohamed, Omar W.A.; FadlElmola Ahmed, Mohammed; Elradi, WalaEldin O. (International Journal of Clinical and Biomedical Research, 2017)
Background: Viral oncogenesis has remained an area of interest in cancer biology. Viruses have been great tutors of cancer biology, helping researchers to uncouple many signaling pathways and identifying critical therapeutic targets. Aim: The aim of this study was to assess the incidence of cytomegalovirus (CMV) infection and its impact on hematological prognostic markers of Acute Myeloid Leukemia (AML) among Sudanese populations. Method: The seroprevlance of CMV infection in AML patients was assessed in 100AML and 100 age and gender-matched controls. The associations of total white cell count and absolute blast count with the seroprevlance were examined. Results: The prevalence of CMV infection was 81% in patients and 17% in control subjects. Total white cell count and blast count were higher in AML CMV positive patients than AML CMV negative patients. Conclusion: Our findings indicate a high incidence of CMV infections in AML and its worse association with hematological markers could emphasize the role of CMV in the progression of AML. KEYWORDS: Acute myeloid leukemia; Cytomegalovirus.